Ester Boserup’s Legacy on Sustainability Orientations for Contemporary Research - Fischer-Kowalski, Marina; Reenberg, Anette; Schaffartzik, Anke; Mayer, Andreas (Human-Environment Interactions, 2014)
Arising from a scientific conference marking the 100th anniversary of her birth, this book honors the life and work of the social scientist and diplomat Ester Boserup, who blazed new trails in her interdisciplinary approach to development and sustainability.   The contents are organized in three sections reflecting important focal points of Boserup’s own work: Long-Term Socio-Ecological Change; Agriculture, Land Use, and Development; and Gender, Population, and Economy. The first three chapters offer a comprehensive review of her political and scientific work. Section Two focuses on the applicability of Boserup’s reflections on land use, technology, and agriculture, incorporating case studies which illuminate and test Boserup’s hypotheses on land use intensification and soil degradation, the impact of population growth on land use, the agricultural transition, and the role of women in development. The case studies examine both long historical time series and present-day dynamics, and explore different levels of geographical scale, from the local to the regional and the global. Section Three emphasizes the key role of women and gender relations for agriculture and development. Together, the 15 chapters in this volume show how the main strands of Boserup’s theories are reflected in contemporary research.   In sum, the diversity of the contributions to this book reflects the continuing impact of Ester Boserup’s work on scientific research today, and its likely influence on research for years to come.